2014
DOI: 10.1038/srep06687
|View full text |Cite
|
Sign up to set email alerts
|

Higher resolution stimulus facilitates depth perception: MT+ plays a significant role in monocular depth perception

Abstract: Today, we human beings are facing with high-quality virtual world of a completely new nature. For example, we have a digital display consisting of a high enough resolution that we cannot distinguish from the real world. However, little is known how such high-quality representation contributes to the sense of realness, especially to depth perception. What is the neural mechanism of processing such fine but virtual representation? Here, we psychophysically and physiologically examined the relationship between st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…They found that 60cpd or higher is required as the resolution for visual realness. It is also shown that high resolution beyond the visual acuity acts as depth perception [3][4]. This is considered as a higher level of perception studied by previous resolution displays up to 4K.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…They found that 60cpd or higher is required as the resolution for visual realness. It is also shown that high resolution beyond the visual acuity acts as depth perception [3][4]. This is considered as a higher level of perception studied by previous resolution displays up to 4K.…”
Section: Introductionmentioning
confidence: 84%
“…In the preceding study [1], 60 cpd twice as many as 30 cpd shows that realness increases and further cpd is recognized as depth. However, the size of the display used in the study is small and compared only to actual objects, and depth perception is limited by the cylinder of the grey scale [3][4]. We tested the viewing angle using a high-resolution display that is identical to normal TV and verified its effect by using real images, not just graphic images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This shows that luminance contrast improvement with a more than 8 K resolution increase leads to a distinct separation of the central object and the background, improves the 3D-ness, and expresses the visual information of the object surface in greater detail, thereby also improving the realness. As 4 K UHD TVs have been commercialized and are currently widely used, their psychological effects have been studied in various aspects [4][5][6]10]. As a result, a high resolution above 4 K is required to improve the depth perception and visual realness.…”
Section: Discussionmentioning
confidence: 99%